Evidence of excess oxygen accommodation in yttria partially-stabilized zirconia. (15th January 2020) - Middleburgh, Simon C.; Ipatova, Iuliia; Evitts, Lee J.; Rushton, Michael J.D.; Assinder, Ben; Grimes, Robin W.; Lee, William E.
Abstract: Yttria partially stabilized zirconia (ZrO2 )x (Y2 O3 )½-x has been investigated to understand accommodation of excess oxygen into its structure. ZrO2 powder with 8 wt% Y2 O3 additions was treated in 30 vol% H2 O2 solution to promote oxidation of the material. A new Raman peak was observed after treatment at 840 cm −1, consistent with previous reports of solid state peroxide ions (O2 2− ). This was corroborated using atomic scale simulation based on density functional theory; these also highlighted the near-zero solution enthalpy for excess oxygen in the monoclinic structure via the formation of a peroxide ion defect. Graphical abstract: Excess oxygen accommodation in yttria partially stabilized zirconia through peroxide ion defects.Unlabelled Image